A Strongly Emitting Liquid‐Crystalline Derivative of Y3N@C80: Bright and Long‐Lived Near‐IR Luminescence from a Charge Transfer State1. Issue 47 (7th October 2013) - Toth, Kalman; Molloy, Jennifer K.; Matta, Micaela; Heinrich, Benoît; Guillon, Daniel; Bergamini, Giacomo; Zerbetto, Francesco; Donnio, Bertrand; Ceroni, Paola; Felder‐Flesch, Delphine
<x xml:space="preserve">Abstract</x> Great balls of fire: C60 and Y3N@C80 were connected to the same oligo(phenyleneethynylene) unit to investigate their structural and photophysical properties. NMR investigations revealed a fulleroid structure for the Y3N@C80 derivative, and both dyads gave rise to columnar phases with core‐shell cylinders. The black and gray spheres represent the fullerene core units of the Y3N@C80 derivative, which is an ideal candidate to be involved in energy and electron transfer processes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>